Hipertensi sebagai Determinan Kerentanan Fungsional pada Populasi Lanjut Usia: A Cross-sectional Study: Hypertension as a Determinant of Functional Vulnerability in the Older Population: A Cross-Sectional Study - Irfan; Rijal (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2026)
The rapid growth of the elderly population in Indonesia has increased the burden of chronic diseases, including hypertension. In addition to being a major risk factor for cardiovascular diseases, hypertension is also believed to be associated with functional decline, which may negatively impact quality of life among older adults. This study aimed to assess the relationship between hypertension and functional impairment among older adults in Indonesia using a cross-sectional design and secondary data from the 2023 Indonesian Health Survey (SKI 2023). This study used a descriptive cross-sectional design. A total of 97,339 individuals aged 60 years and older were included in the analysis. Hypertension status was determined based on a history of medical diagnosis by a physician, while functional status was assessed using the Barthel Index. Data were analyzed using Spearman’s correlation test. The prevalence of hypertension among older adults was 21.9%, with higher rates observed in the 75–89 years age group (24.8%) and among females (26.2%). Most participants were functionally independent (80.0%), while the remainder exhibited varying levels of dependency. Statistical analysis revealed a significant correlation (p < 0.001) between the level of hypertension and functional impairment among older adults; however, the strength of the correlation was weak (r = 0.102). These findings indicate that hypertension is associated with an increased risk of functional limitations among older adults. ABSTRAK Pertumbuhan populasi lansia di Indonesia yang sangat pesat telah meningkatkan beban penyakit kronis, termasuk hipertensi. Selain menjadi faktor risiko utama penyakit kardiovaskular, hipertensi juga diyakini berhubungan dengan penurunan fungsi, yang dapat berdampak negatif terhadap kualitas hidup pada kelompok usia lanjut. Penelitian ini bertujuan untuk menilai hubungan antara hipertensi dan gangguan fungsional pada lansia di Indonesia dengan menggunakan desain potong lintang dan data sekunder dari Survei Kesehatan Indonesia (SKI) 2023. Penelitian ini merupakan penelitian deskriptif dengan pendekatan cross-sectional study. Jumlah sampel yang terlibat sebanyak 97.339 individu berusia 60 tahun ke atas. Instrumen yang digunakan untuk status hipertensi yaitu berdasarkan riwayat diagnosis medis (dokter), sedangkan status fungsional dinilai menggunakan Indeks Barthel. Analisis data menggunakan korelasi Spearman. Prevalensi hipertensi pada lansia adalah 21,9%, dengan angka lebih tinggi pada kelompok usia 75–89 tahun (24,8%) dan pada perempuan (26,2%). Sebagian besar peserta berada pada kategori mandiri secara fungsional (80,0%), sementara sisanya menunjukkan tingkat ketergantungan yang bervariasi. Analisis statistik menunjukkan adanya korelasi yang signifikan (p<0.001) atara tingkat hipertensi dan gangguan fungsional pada lansia, namun dengan koefisien korelasi yang lemah (r = 0,102). Temuan ini mengindikasikan bahwa hipertensi terkait dengan peningkatan risiko keterbatasan fungsi pada lansia.